The cleanliness and purity of ablution and toilet area in masjid: an analysis of users’ understanding and behaviour - Abdullah, Siti Hanisah; Abdul Rahim, Asiah (Abdullatif Al Fozan Award for Mosque Architecture and Institut Terjemahan & Buku Malaysia Berhad, 2019)
INTRODUCTION: ONE of the best good that a person can do is the upkeep and sustaining of masjid as bountiful in return are promised (Hasan Lam, 2018). Believers should exercise the above mentioned in accommodating “Allah’s guest” as well as in enhancing the quality of ibadah (worship). As commanded by Allah SWT to Prophet Ibrahim in Surah Al-Hajj, verse 26: “Purify My House for those who circle around it, those who stand to pray, and those who bow and prostrate themselves”. An encryption of morals was scripted “under the guardianship of Prophet Muhammad, peace and blessings be upon him (PBUH), and divine revelation” (Omer, 2017). Omer explained that this scripture served as a guideline enhancing the development of masjid and the practices in it. Among which preservation of the cleanliness of masjid was detailed “for cleanliness is part of faith”. Harmoniously, the requisite for one to prostrate before the Almighty, his figure, cloth, and space of worship must be pure (Baz, 2007).